KONTRIBUSI PEMBINAAN KEPALA SEKOLAH, SARANA PRASARANA DAN KESEJAHTERAAN GURU TERHADAP PRODUKTIVITAS KERJA GURU SD SE KECAMATAN JETIS KOTA YOGYAKARTA TAHUN 2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The research was intended to identify (a) simultaneously contribution of principals development for teacher, facilities and teacher welfare on teacher working productivity (b) partial contribution of principal development for teacher on teacher working productivity (c) partial contribution of facility on teacher working produtivity and (d) partial contribution of teacher welfare on teacher working productivity. The population of this research were all of primary school teachers in Jetis district Yogyakarta which totally 251 persons. The sample was 156 persons which was taken by Nomogram Harry King formula at the 5% signification with Proportionate Random Sampling technique. In collecting data the researcher used questionaire. The data analysis technique used multiple regression and partial correlations with level significancy is 5%. The result of research indicated that (a) there is significantly positive contribution of principal development for teacher, facilities, and teacher welfare on teacher working productivity in simultaneous manner. It means that increase and decrease in teacher working productivity one of which is determined by the principal development for teacher, facilities, and teacher welfare, (b) there is significantly positive partial contribution of principal development for teacher on teacher working productivity. Better principal development for teacher will support the teacher working productivity (c) there is significantly positive partial contibution of facilities on teacher working productivity. Better facilities will support teacher working produktivity. (d) there is significantly positive partial contribution of teacher welfare on teacher working productivity. Better teacher welfare will support teacher working productivity.